The Analysis of Psychopathic Traits and Behavioral Problems Relationships in Italian Adolescents - Rossi, Luca; Zanetti, Margot (Journal of Education and Training, 2021)
In this article we analysed the association between psychopathic traits manifested at early age and behavioral problems in adolescents with an extension of correspondence analysis. The used technique allows to verify the relationship between row and column variables in a two-way contingency table. The data are obtained submitting to a sample of 689 high school students two questionnaires: The Inventory of Callous-Unemotional Traits (ICU) and The Strengths and Difficulties Questionnaire (SDQ)). Founding has an important pedagogical impact. The educational professionals, who spend most of the day with the kids, hardly can identify the Callous-unemotional traits but, at same time, could identify easily behavioral problems allowing the implementation of early treatments or the use of pedagogical strategies for young people that could have a high risk of psychopathic traits.